2019
DOI: 10.1021/acs.analchem.8b05538
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nanopillar Chips for Continuous Separation of Extracellular Vesicles

Abstract: Micro-and nanopillar chips are widely used to separate and enrich biomolecules, such as DNA, RNA, protein, and cells, as an analytical technique and to provide a confined nanospace for polymer science analyses. Herein, we demonstrated a continuous accurate and precise separation technique for extracellular vesicles (EVs), nanometer-sized vesicles (typically 50−200 nm) currently recognized as novel biomarkers present in biofluids, based on the principle of electroosmotic flow-driven deterministic lateral displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…Hattori et al successfully separated 50 and 200 nm NPs using micro-and nano-pillar chips on an electroosmotic flow (EOF)-driven DLD, and also roughly separated EVs below and above 400 nm in size. Similarly, those authors could not change the size distribution of the exosomes so much before and after sorting, either [26]. Zeming et al also reported the separation of 51 and 190 nm NPs using DLD devices under different ionic concentrations.…”
Section: Introductionmentioning
confidence: 89%
“…Hattori et al successfully separated 50 and 200 nm NPs using micro-and nano-pillar chips on an electroosmotic flow (EOF)-driven DLD, and also roughly separated EVs below and above 400 nm in size. Similarly, those authors could not change the size distribution of the exosomes so much before and after sorting, either [26]. Zeming et al also reported the separation of 51 and 190 nm NPs using DLD devices under different ionic concentrations.…”
Section: Introductionmentioning
confidence: 89%
“…invented an electroosmotic flow‐driven DLD method to isolate EVs continuously (Figure 2e ), which possessed an easy‐to‐operate flow control compared to the traditional DLD procedure. [ 64 ] The DLD procedures showed good potential for size‐based EV isolation. However, other characteristics of EVs, such as density and stiffness, are non‐negligible interference factors in DLD‐based EV isolation.…”
Section: Advanced Nanotechnologies For Ev Isolationmentioning
confidence: 99%
“…e) Electroosmotic flow driven-deterministic lateral displacement. Reproduced with permission [64]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…Current methodologies for EV separation are mainly divided into three groups: 82 density-based separation using ultracentrifugation; 83 size-based separation using size exclusion chromatography; and immunoaffinity-based separation (for specific membrane proteins, e.g., CD9, CD63, and CD81). As emerging alternatives, microfluidicbased platforms (density-, immunoaffinity-, and size-based separations) 84,85 have been reported. The EV subsets obtained through density-, size-, and immunoaffinity-based separations have been extensively studied, but fewer efforts have been devoted to investigating the correlation between EV subsets obtained through surface charge-based separation and encapsulated miRNAs or expressed membrane proteins.…”
Section: Ev Separation Using Nanowiresmentioning
confidence: 99%